Integrin-alpha-6+ Candidate stem cells are responsible for whole body regeneration in the invertebrate chordate Botrylloides diegensis - Kassmer, Susannah H. (Nat Commun, 2020)
Colonial ascidians are the only chordates able to undergo whole body regeneration (WBR), during which entire new bodies can be regenerated from small fragments of blood vessels. Here, we show that during the early stages of WBR in Botrylloides diegensis, proliferation occurs only in small, blood-borne cells that express integrin-alpha-6 (IA6), pou3 and vasa. WBR cannot proceed when proliferating IA6+ cells are ablated with Mitomycin C, and injection of a single IA6+ Candidate stem cell can rescue WBR after ablation. Lineage tracing using EdU-labeling demonstrates that donor-derived IA6+ Candidate stem cells directly give rise to regenerating tissues. Inhibitors of either Notch or canonical Wnt signaling block WBR and reduce proliferation of IA6+ Candidate stem cells, indicating that these two pathways regulate their activation. In conclusion, we show that IA6+ Candidate stem cells are responsible for whole body regeneration and give rise to regenerating tissues.